Cumulative Stressors in Preterm Infants Hospitalized in Neonatal Intensive Care Units - Rahkar Farshi; Jabraeili; Sabouhi; Ghorbani (Kashan University of Medical Sciences, 2016)
Background Infants' exposure to stressors in neonatal intensive care unit (NICU) and its outcomes is a new issue since previous studies have only focused on painful stimuli. Taking into account frequency and severity of the stressors on each infant, short and long-term outcome of these stressors can be improved. Objectives This study aimed to evaluate the cumulative stressors in premature infants hospitalized in a NICU. Methods In this descriptive study, 197 hospitalized preterm infants between 28 to 30 weeks of gestation were studied in terms of cumulative stressors during 10 days at the NICU of Tabriz Alzahra hospital. Consecutive sampling method was used. Demographic questionnaire and neonatal infant stressor scale were used. Descriptive statistics, repeated measures analysis and Pearson's correlation coefficient tests were used to analyze the data. Results The total mean of stress scores during 10 days was 99.44 ± 17.37. "Multiple attempts to insert intravenous and intra-arterial catheters and "intubation" were the most frequent procedures in the "extremely stressful" category among four categories of stressors. The highest scores of acute and chronic stress were related to the tenth and third day of hospitalization, respectively. There was no significant difference between infants' characteristics and total mean stress scores. Repeated measures analysis showed that the mean acute stress scores were significantly different among the 10 subsequent days (P < 0.05). Conclusions The results of this study demonstrated the frequent occurrence of various procedures in preterm infants hospitalized at the NICU. Although these procedures were done with the purpose of improving infants' health, they can lead to problems and complications, which might postpone the infants' recovery process.